Religion, globalization and culture - Beyer, Peter, 1949-; Beaman, Lori G. (International studies in religion and society, 2007)
The topic of religion and globalization is complex, susceptible to a variety of approaches. This volume brings together over 25 articles by many of the important authors who have worked on issues directly related to the theme of religion and globalization.